Effect Of Using Hallux Valgus Splint On Hallux Valgus Pain In - Muh. Syaiful Akbar; Dwi Setyawan; Humaidah Azzahra (Proceedings of Malikussaleh International Conference on Health and Disaster Medicine (MICOHEDMED), 2022)
Abstract: Female teachers often use high heels in their work activities, which causes musculoskeletal problems such as hallux valgus. Hallux valgus can cause pain around the first metatarsophalangeal joint. One of the treatments for hallux valgus is a hallux valgus splint which works as a big toe corrector. This study aims to determine the effect of using hallux valgus splints on pain due to hallux valgus on teachers and employees at public elementary schools in the Kemangkon district. Purpose: The purpose of this study was to determine the effect of using a hallux valgus splint on pain due to hallux valgus in teachers and employees at State Elementary Schools in Kemongkon District. Patients and methods: This research is a quasi-experimental research with one group pre and posttest design. The subjects in this study were teachers and employees at a public elementary school in the Kemangkon district as many as 22 people with hallux valgus pain. Subjects were given an intervention using a hallux valgus splint and pain measurements were made using a numeric rating scale (NRS). Results: Hypothesis testing using paired sample t-test showed that the use of hallux valgus splint could reduce hallux valgus pain p = 0.000 (p <0.05), statistically there was an effect. Conclusion: It can be concluded that there is an effect of using a hallux valgus splint on pain due to hallux valgus on teachers and employees at public elementary schools in Kemangkon District